1996
DOI: 10.1073/pnas.93.6.2312
|View full text |Cite
|
Sign up to set email alerts
|

beta-Amyloid toxicity in organotypic hippocampal cultures: protection by EUK-8, a synthetic catalytic free radical scavenger.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(147 citation statements)
references
References 45 publications
9
136
0
2
Order By: Relevance
“…ER stress has been shown to play a pivotal role in Aβ-induced neurotoxicity (10) and AD pathology (11,12). In our previous experiments, we also showed that exposure of cultured hippocampal neurons to Aβ or Aβ [25][26][27][28][29][30][31][32][33][34][35] resulted in an increase of cell death in a timeand concentration-dependent manner and in destruction of neuronal integrity with a significant increase in the level of glucose-regulated protein 78 (GRP78), known to be a molecular chaperone that regulates protein folding and translocation into the ER (3,4), suggesting that the cellular insults elicited by these agents involves ER stress in cultured hippocampal neurons. However, the exact molecular mechanisms that underlie Aβ-induced neuronal death are still not completely understood.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…ER stress has been shown to play a pivotal role in Aβ-induced neurotoxicity (10) and AD pathology (11,12). In our previous experiments, we also showed that exposure of cultured hippocampal neurons to Aβ or Aβ [25][26][27][28][29][30][31][32][33][34][35] resulted in an increase of cell death in a timeand concentration-dependent manner and in destruction of neuronal integrity with a significant increase in the level of glucose-regulated protein 78 (GRP78), known to be a molecular chaperone that regulates protein folding and translocation into the ER (3,4), suggesting that the cellular insults elicited by these agents involves ER stress in cultured hippocampal neurons. However, the exact molecular mechanisms that underlie Aβ-induced neuronal death are still not completely understood.…”
Section: Introductionmentioning
confidence: 83%
“…In OHCs cultured for 7 weeks, S-allyl-L-cysteine (SAC), a component of aged garlic extract, protected the cells in areas CA1 and CA3 and the dentate gyrus from Aβ 25-35 -induced toxicity. The immunoreactivity of cleaved caspase-12 was increased whereas that of glucose-regulated protein 78 was not altered after exposure to Aβ [25][26][27][28][29][30][31][32][33][34][35] . The increases in the cleaved caspase-12 were also reversed by simultaneously applied SAC.…”
mentioning
confidence: 96%
“…Ebselen is a selenium-containing organic compound that mimics the action of glutathione peroxidase (Wendel et al 1997). Diosgenin is a plant-derived steroid (Accatino et al 1998) and EUK 8 is a synthetic manganese complex that has previously been shown to protect against amyloid beta toxicity and stroke via antioxidative mechanisms (Bruce et al 1996). Although mitochondria may be an important source of ROS under pathological conditions (Dykens 1997), the prevention of MA + Tat-induced reduction of Y by these antioxidants suggests that oxidative stress precipitates rather than results from mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation of A/3 in vitro is catalyzed by oxidation and is inhibited by antioxidants (Dyrks et al, 1992). A/3 neurotoxicity is attenuated by a number of antioxidants (e.g., vitamin E and EUK-8) (BehI et al, 1992;Bruce et al, 1996). A/3 itself induces reactive oxygen species (Behl et al, 1994;Goodman and Mattson, 1994;Goodman et al, 1994).…”
mentioning
confidence: 99%